WHEN THE TIDE LOWS: THE SOCIOCULTURAL MEANINGS OF “BABA DO VINHO” FROM THE “AMIGOS DO ACUPE” IN PIATÃ, SALVADOR, BAHIA - Caldas, Francisco Demetrius Luciano (2023)
In Salvador, capital of the state of Bahia, an amateur soccer group called Amigos do Acupe have been playing fortnightly games on the sands of Piatâ beach for more than twenty years, and in particular a unique game during Holy Week, popularly known as Baba do Vinho or Baba do Vinho. Sai Baba. The objective of this article is to interpret the sociocultural meanings of this soccer match that takes place during the leisure time of its members on the Saturday of Hallelujah of the Catholic holiday and that, being a beach soccer, depends on the movement of the tides, both in its routine games, as well as on this festive day. The methodology was guided by ethnography with the use of participant observation, field diary and interviews. The results revealed the Baba do Vinho dos Amigos do Acupe as a space for male sociability in the sports and religious culture of the beach and pointed out distinctions between the group's habit of experiencing tradition and other formats of this ritual game spread across the city's neighborhoods. Such differences triggered dialogues with social constructions about masculinity and gender.